PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, KODE ETIK AKUNTAN, STANDAR AKUNTANSI PEMERINTAH DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Abdul Lathif; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
This study aims to determine: (1) The influence of human resource competence on the quality of regional financial statements, (2) The influence of the Accountant Code of Ethics on the quality of regional financial reports, (3) The effect of the application of government accounting standards on the quality of regional financial statements, (4) The effect of the application of the regional financial accounting system on the quality of the regional financial statements, (5) The effect of the application of the competence of human resources, the code of ethics of accountants, the application of government accounting standards, the application of the regional financial accounting system to the quality of regional financial statements. This research is a quantitative study, the population in this study was 22 SKPD in Malang district government. Data collection techniques with questionnaires distributed to 66 respondents. Test data quality using validity and reliability. Analysis prerequisite tests include normality test, multicollinearity test, heteroscedasticity test. Data analysis techniques using simple regression analysis techniques and multiple linear regression analysis. The results of this study are there are influences on human resource competence, accountant code of ethics, SAP application, and application of regional financial accounting systems to the quality of regional financial reports. F test results showed an F value of 7.203, and Sig.F of 0.000, therefore H0 was rejected and H1 was accepted. Keywords: Quality of regional financial statements, code of ethics of accountants, application of SAP and application of a regional financial accounting systems.